Southernmost Asia is the source of Japanese encephalitis virus (genotype 1) diversity from which the viruses disperse and evolve throughout Asia. - Xiaoyan Gao; Hong Liu; Huanyu Wang; Shihong Fu; Zhenyang Guo; Guodong Liang (Public Library of Science (PLoS), 2013)
BACKGROUND: Although a previous study predicted that Japanese encephalitis virus (JEV) originated in the Malaysia/Indonesia region, the virus is known to circulate mainly on the Asian continent. However, there are no reported systematic studies that adequately define how JEV then dispersed throughout Asia. METHODOLOGY/PRINCIPAL FINDINGS: In order to understand the mode of JEV dispersal throughout the entire Asian continent and the factors that determine the dispersal characteristics of JEV, a phylogenetic analysis using Bayesian Markov chain Monte Carlo simulations was conducted on all available JEV E gene sequences in GenBank, plus strains recently isolated in China. Here we demonstrate for the first time that JEV lineages can be divided into four endemic cycles, comprising southern Asia, eastern coastal Asia, western Asia, and central Asia. The isolation places of the viruses in each endemic cycle were geographically independent regardless of years, vectors, and hosts of isolation. Following further analysis, we propose that the southernmost region (Thailand, Vietnam, and Yunnan Province, China) was the source of JEV transmission to the Asian continent following its emergence. Three independent transmission routes from the south to north appear to define subsequent dispersal of JEV. Analysis of JEV population dynamics further supports these concepts. CONCLUSIONS/SIGNIFICANCE: These results and their interpretation provide new insights into our understanding of JEV evolution and dispersal and highlight its potential for introduction into non-endemic areas.